Modeling of insulin sensitivity for Sepsis-AKI and Sepsis Non-AKI - Farhah, M.; Fatanah, M. S.; Mohd Zulfakar, M.; Ummu Kulthum, Jamaludin; Normy, R.; Syatirah, M. Z.; Jihan, M. Z.N. (Institute of Electrical and Electronics Engineers Inc., 2022)
Sepsis-induced acute kidney injury (SAKI) patients are linked to high rates of death and morbidity. Additionally, infection and injury increase blood glucose levels, making glycemic control difficult. To control the glycemic level, insulin therapy is required to maintain blood glucose in a normal range. Hence, this study intended to investigate the sepsis and AKI factors in blood glucose outcomes, especially for successful glycemic control. In this study, blood glucose level, insulin administration, and insulin sensitivity between sepsis-AKI And sepsis non-AKI were compared, along with the stochastic model of the two cohorts. Using retrospective clinical data of 20 ICU patients aged 18 years old and above from Hospital University Sains Malaysia from September to November 2021, 10 sepsis AKI patients spent longer total treatment hours (2526) and longer length of stay (median = 8 days) and had a higher median APACHE II score (median = 28) compared to sepsis non-AKI. Additionally, they had higher blood glucose levels per cohort (median = 9.8mmol/L) and higher insulin administration (median = 0.5 U/hr). However, the statistical analysis determined no significant difference between sepsis AKI and sepsis non-AKI in blood glucose level per cohort, per patient metrics, insulin sensitivity, and insulin dosage. In conclusion, it can be concluded that sepsis contributes much to reducing insulin sensitivity and thus plays an important role in affecting the blood glucose level. Clinical Relevance - This demonstrates that, despite AKI, sepsis had more impact on insulin sensitivity and plays an essential role in blood glucose outcome and the success of glycemic control.